71‐2: Enabling Processes and Designs for Tight‐Pitch Micro‐LED based Stretchable Display. Issue 1 (28th June 2021) - Kang, Jiahao; Luo, Haojun; Tang, Weihuang; Zhao, Jigang; Wang, Yu-Min; Tsong, Tina; Lu, Ping; Gupta, Amit; Zeng, Lu; Zhang, Zhao; Zhou, Jinjie; Wang, Shaowen; et al.
Abstract : This work presents a stretchable micro‐LED display technology which is scalable and compatible with industrial manufacturing processes. The enabling processes and design methods are introduced. Utilizing 90×150‐µm RGB LEDs, a 2.7‐inch 42‐PPL stretchable display panel is demonstrated.